Avaliação de carcarça de cordeiros alimentados com dietas a base de silagem de sorgo realocada e níveis de concentrado - Cruz, Antoniel Florencio da (2022)
In confinement systems, maximizing animal performance is one of the essential strategies for the viability of the production system. Therefore, the inclusion of concentrates is an important strategy that favors greater fat deposition and weight gain. Thus, the objective of this work was to evaluate the inclusion of concentrate levels in diets for beef sheep on carcass characteristics. The experiment was conducted at the Scientific Research Institute (Embrapa Semiárido), located in the city of Petrolina-PE. Twenty-eight non-castrated lambs, without defined breed standard (SPRD) with average initial body weight of 18.43±2.3kg were used, distributed in a completely randomized design (DIC), with four treatments (T1: 43% of concentrated supplement; T2: 66% concentrated supplement; T3: 81% concentrated supplement; T4: 91% concentrated supplement based on dry matter) and eight replicates. You animals were confined for 60 days until slaughter. The inclusion of concentrate affected the empty carcass weight (EWC) (P=0.0493), with an increase in EBW, the measure that increased the inclusion of concentrate. For hot carcass weight (PCQ) a quadratic effect was found (P=0.0291) and there was maximization when 71.65% of concentrate was included in the diet. There were no effects of concentrate levels on neck (P=0.1979), rib (P=0.5460), shoulder (P=0.5684), loin (P=0.1046) and leg (P=0.9716), as well as gastro intestine tract weight (P=0.3220) and loin eye area (P=0.6013). There was a decreasing linear effect on hepatic glycogen, the histopathological deleterious effect on the kidneys, with an increase in epithelium thickness, keratinized portion, area of papillae and width of rumen papillae. Goblet cells increased in number in the animals up to 81% concentrate. The inclusion of concentrate contents between 60 and 72% of concentrate based on the dry matter of the feed in diets based on reallocated sorghum silage provides higher yields and carcass quality of sheep. The effects for digestibility and absorption of nutrients when considering the structures of the gastrointestinal tract were better for the inclusion between 81% and 91% of concentrate.